ANALISIS PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KAMPUNG KERAJINAN BAMBU DAN ROTAN DI KELURAHAN PAKINTELAN KECAMATAN GUNUNGPATI KOTA SEMARANG - Goretty Situmorang, Maria; Nurcahyanto, Herbasuki; Marom, Aufarul (Journal of Public Policy and Management Review, 2024)
The analysis of community empowerment through the Bamboo and Rattan Craft Village Program is based on developing efforts to improve the community's economy. The problems with this research are that management is not yet fully structured, there is a lack of socialization and training, limited facilities and infrastructure, a lack of interest from the community or young people, and a lack of involvement of interested actors. The aim of this research is to analyze empowerment efforts as well as factors inhibiting the sustainability of empowerment. The effort in question uses the Stages of Community Empowerment theory put forward by Wrihatnolo and Dwidjowijoto using a descriptive research method with a qualitative approach. Data was obtained through interviews, observation, and documentation. The research results show that community empowerment has carried out the stages of empowerment well. It can be seen in three stages, namely the awareness stage in the form of socialization regarding empowerment and community interest in participating. The capacitybuilding stage takes the form of providing training to the community and reducing assistance from the government to support the implementation of empowerment. Empowerment Stage by introducing social media and achieving results and output from community empowerment. The stages of an effort have not been fully achieved due to community involvement and the quality of human resources, the limited role of each interested actor, limited facilities and infrastructure, and minimal communication. It is recommended to increase the role of actors, increase the availability of facilities and infrastructure, utilize existing facilities, establish relationships and cooperation, and conduct training so that it can be implemented optimally.